Allelic distributions of CYP2D6 gene copy number variation in the Eastern Han Chinese population - Sheng Hai-hui; Zeng Ai-ping; Zhu Wen-xiang; Zhu Ren-fang; Li Hong-mei; Zhu Zhi-dong; Qin Ying; Jin Wei; Liu Yan; Du Yun-lan; Sun Jian; Xiao Hua-sheng (Acta Pharmacologica Sinica, 2016)
Aim: The human cytochrome P450 2D6 (CYP2D6) gene copy number variation, involving CYP2D6 gene deletion (CYP2D6*5) and duplication or multiduplication (CYP2D6*×N), can result in reduced or increased metabolism of many clinically used drugs. The identification of CYP2D6*5 and CYP2D6*×N and the investigation of their allelic distributions in ethnic populations can be important in determining the right drug and dosage for each patient. Methods: The CYP2D6*5 and CYP2D6 genes, and CYP2D6 gene duplication were identified by 2 modified long PCR, respectively. To determine duplicated alleles, a novel long PCR was developed to amplify the entire duplicated CYP2D6 gene which was used as template for subsequent PCR amplification. A total of 363 unrelated Eastern Han Chinese individuals were analyzed for CYP2D6 gene copy number variation. Results: The frequency of CYP2D6*5 and CYP2D6*×N were 4.82% (n=35) and 0.69% (n=5) in the Eastern Han Chinese population, respectively. Of the 5 duplicated alleles, 3 were CYP2D6*1×N and 2 were CYP2D6*10×N. One individual was a carrier of both CYP2D6*5 and CYP2D6*1×N. Taken together, the CYP2D6 gene rearrangements were present in 10.74% of subjects. Conclusion: Allelic distributions of the CYP2D6 gene copy number variation differ among Chinese from different regions, indicating ethnic variety in Chinese. Long PCR are convenient, cost effective, specific and semiquantitative for the detection of the CYP2D6 gene copy number variation, and amplification of the entire duplicated CYP2D6 gene is necessary for the accurate identification of duplicated alleles.